Synthesis and Characterization of NaOH-Doped ZnO Metal Oxide Thin Films for Electron Transport Layer in Dye-Sensitized Solar Cells (DSSCs) - W. S. Arsyad; H. A. Hangkea; I. Saleh; I N. Sudiana; L. Agusu; I. Usman (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
Research on the manufacture of ZnO thin films as electron transport layers has been carried out. The ZnO coating was prepared by sol-gel method. At the time of making the solution precursor, the doping given was 0.72%, 1.09%, and 1.45% by weight. Each hkl index changes at an angle of 2θ which causes the mean crystal size to decrease from 57.57 nm, 35.94 nm to 24.01 nm for doping concentrations of 0.72%, 1.09% and 1.45%, respectively. The measurement results using the LCR meter show that the resistance of the ZnO thin layer increases with the addition of NaOH doping from 125.49 Ω.cm, 462.93 Ω.cm and 3192.8 Ω.cm for doping are 0.72%, 1.09% and 1.45% NaOH respectively. The results of the analysis of the UV-Vis spectrometer, the slit energy value decreased with the increase in the doping of NaOH given, namely 2.03 eV, 2.026 eV, 2.025 eV and 2.024 for samples without doping are 0.72%, 1.09% and 1.45% sequentially. The results of the morphological analysis using SEM showed that the grains with sizes and shapes tended to be the same in all thin film samples.